RIGHT TO ACCESS INFORMATION IN DECENTRALIZED INDONESIA: A SOCIO-LEGAL INQUIRY - Perdana Wiratraman, Herlambang; El Muhtaj, Majda; Kasim, Ifdhal (Jurnal Media Hukum, 2015)
Indonesia is no longer an authoritarian country, and no longer centralized government. Decentralization processes since 1999 has changed local democratization in a wider participation. Nevertheless, the culture of openness and incorrupt have been far from the more ideal situation. Bribery, corruption and unresponsive public services have been continuously and more systematic taking place. In that context, the Government of Indonesia enacted Law No. 14 of 2008 concerning Public Information Openness (Keterbukaan Informasi Publik or called PIO Law), which is implemented since 30 April 2010. The PIO law is believed to contribute to the better decentralization processes and economic-political democratization at local level. Nevertheless, although right to access information was guaranteed by law, but it has been applied in limited process. Such situation actually gives clear evidence that decentralized Indonesia should be questioned, especially in terms of how the right to access information has been applied in a meaningful way after the enactment PIO Law in 2008 and, what the dominant problems in implementing right to access information are. This article will elaborate the norms and practices of PIO Law by using the rule of law point of view.